Reification in Harriet Beecher Stowe’s Uncle Tom’s Cabin - yono, Hari; Handoko, Putut (Dinamika : Jurnal Sastra dan Budaya, 2019)
This research studied reification in Harriet Beecher Stowe’s Uncle Tom’s Cabin. The researchers used reification theory as proposed by Georg Lukacs and within Marxist tradition. By using Lukacs points of reification of the three points, the researchers find that Uncle Tom experiences the three points of reification, those are depersonalization, alienation of labor, and thing-like relation.